2018
DOI: 10.1080/00016357.2018.1440322
|View full text |Cite
|
Sign up to set email alerts
|

A high prevalence of TMD is related to somatic awareness and pain intensity among healthy dental students

Abstract: The prevalence of any DC/TMD diagnosis was 30%. The most prevalent TMD diagnosis was myalgia. Individuals with a TMD-pain diagnosis (i.e. myalgia or arthralgia) reported significantly higher pain intensity levels according to the Graded Chronic Pain Scale (GCPS) as compared to individuals without TMD-pain (Fisher's exact test p < .001, two-sided). In addition, individuals with any TMD scored significantly higher jaw functional limitations according to the Jaw Functional Limitation Scale 20 (JFLS-20, p < .001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
33
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
13
33
2
3
Order By: Relevance
“…It should be noted that the participants were university students (a speci c subgroup of young adults) and a more representative sample would have increased the study validity. Nevertheless, the percentage of students suffering TMD matches population prevalence suggested by other studies [15,36,37,38,39]. Furthermore, participants average score of the psychological questionnaires were similar to other Spanish university students (Spain) according to norms provided by questionnaire manuals [30,31,32], since percentiles where within 40 and 60 (see Table 2), except for anxiety trait and just one of the CRI coping strategy, logical analyses (30 and 35, respectively).…”
Section: Discussionsupporting
confidence: 83%
“…It should be noted that the participants were university students (a speci c subgroup of young adults) and a more representative sample would have increased the study validity. Nevertheless, the percentage of students suffering TMD matches population prevalence suggested by other studies [15,36,37,38,39]. Furthermore, participants average score of the psychological questionnaires were similar to other Spanish university students (Spain) according to norms provided by questionnaire manuals [30,31,32], since percentiles where within 40 and 60 (see Table 2), except for anxiety trait and just one of the CRI coping strategy, logical analyses (30 and 35, respectively).…”
Section: Discussionsupporting
confidence: 83%
“…Based on the epidemiological studies, a broad prevalence peak of TMD symptoms is present between 20 and 40 years of age, with a lower prevalence in younger and older people [11][12] . Many studies published related to the unıversity students of different countries have reported that the TMD prevalence ranged from 17% to 87% due to differences in the populations studied, diagnostic criteria, examination methods, and inter-and/or intra-rated variations of examining practitioners [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various studies on TMD used the JFLS to assess mandibular dysfunction. [13][14][15][16] However, the JFLS was also created in English; therefore, it cannot be used directly in Chinese people.…”
mentioning
confidence: 99%